Implementation Of Emotive Rational Counseling Approach To The Increased Students’ Learning Motivation - Muhammad Syahrul; Andi Bunyamin (JURKAM: Jurnal Konseling Andi Matappa, 2020)
The purpose of this research is to recognize the difference of students' learning motivation in taking mathematics lesson before and after the application of Emotive Rational Counseling. This research includes quantitative research. Sample of the research was 30 students. It was selected by purposive sampling technique. Data was collected by questionnaire. It was then analyzed using descriptive statistical analysis and t-test. The result of this research obtained an experimental subject before taking Emotive Rational counseling of which average value was equal to 61,03. It indicates that the level of student's motivation to participate in math lesson is in low category. After the treatment of Emotive Rational counseling, it obtained an average result of 82.86. It denotes that the students' motivation level is in high category. From the t-test it obtained the value of tcount of 14.620, while the ttable value at the level of significance is 5 percent with dk = 29 of 2.045. It states that the research hypothesis was rational emotive counseling therapy can increase student learning motivation.